Penile Rehabilitation Therapy with PDE-V Inhibitors Following Radical Prostatectomy: Proceed with Caution - M. Eric Brewer; Edward D. Kim (Advances in Urology)
Penile rehabilitation therapy following radical prostatectomy is a much debated topic. Erectile dysfunction is still a significant contributor to postoperative morbidity following radical prostatectomy, despite meticulous nerve-sparing technique. Secondary smooth muscle changes in the penis have been identified as the underlying causes of penile atrophy, veno-occlusive dysfunction, and fibrosis. Initial observations that intracavernous injection therapies used on a regular basis postoperatively resulted in improvements in the return of spontaneous erectile function led to the development of penile rehabilitation protocols. Chronic dosing of PDE-V inhibitors is now commonly used by urologists after radical prostatectomy. Despite the current enthusiasm of penile rehabilitation therapy, current scientific evidence with clinical trials is still limited.